Photon Counting CT: Clinical Applications and Future Developments - Hsieh, Scott S.; Leng, Shuai; Rajendran, Kishore; Tao, Shengzhen; McCollough, Cynthia H. (IEEE transactions on radiation and plasma medical sciences, 2021)
The use of a photon counting detector in CT (PCD CT) is currently the subject of intense investigation and development. In this review article, we will describe potential clinical applications of this technology with a particular focus on the experience of our own institution with a prototype PCD CT scanner. Photon counting detectors (PCDs) have three primary advantages over conventional, energy integrating detectors (EIDs): 1) they provide spectral information without need for a dedicated dual-energy protocol; 2) they are immune to electronic noise; and 3) they can be made very high resolution without significant compromises to quantum efficiency. These advantages translate into several clinical applications. Metal artifacts, beam hardening artifacts, and noise streaks from photon starvation can be better mitigated using PCD CT. Certain incidental findings can be better characterized using the spectral information from PCD CT. High-contrast, high-resolution structures, such as the temporal bone can be better visualized using PCD CT and at greatly reduced dose. We also discuss new possibilities on the horizon, including new contrast agents, and how anticipated improvements in PCD CT will translate to performance in these applications.